Phenomena of Removal of Crystal Violet from Wastewater Using Khulays Natural Bentonite - Saad Al-Shahrani (Journal of Chemistry)
The study investigates the phenomena involved in the crystal violet (CV) removal using the Khulays natural bentonite from the wastewater. The batch technique was utilized for performing the adsorption experiments. The operating systems were used for the investigation of the adsorption behaviour in the study, which included the initial CV concentration, time taken for shaking, the dosage of adsorbent, and the initial solution pH. The Freundlich isotherm framework and the Langmuir data were assessed in the experiment. The study outcome revealed that the equilibrium in the study was reached when shaking takes place for about 40 minutes. Additionally, the data of the sorption revealed that the enhancement of the CV concentration at the start mitigates the percentage of the CV removal as a result of which saturation integration in the Khulays bentonite dye occurs. The initial improvement in the solution pH led to improved CV adsorption. The data achieved at the isotherm adsorption were found adequate with the frameworks of Freundlich isotherm and Langmuir. Along with it, the model of pseudo-second-order kinetics was used to exhibit the adsorption of crystal violet with the Khulays natural bentonite. The Khulays natural bentonite adsorption of CV was demonstrated by the thermodynamic data exhibiting its spontaneous as well as endothermic nature. The study concludes that basic dyes can be effectively removed from the wastewater by the use of Khulays natural bentonite.